Analisis Desain Pembelajaran dengan Pendekatan Deep Learning berbasis ADDIE (Analyze, Design, Develop, Implement, Evaluation) - Kusno Setiadi; Dina Martha (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to analyze learning design with an approachdeep learningbased on the ADDIE model at SDIT Permata Bunda, Rajabasa District. The method used was qualitative research with a case study design. The research subjects were teachers, and the research object was the problem-based learning design.deep learningData were collected through observation, interviews, and document analysis, then analyzed using the Miles and Huberman model. The results showed that in the analysis stage, there was a need to shift from conventional learning to more contextual learning. In the design stage, teachers began to develop holistic learning objectives, while the development stage was characterized by the use of digital media such as video.gameeducational and collaborative platforms. The learning implementation demonstrated increased student participation, particularly in discussions, Q&A sessions, and real-world problem-solving. Evaluation was conducted through observation, portfolios, projects, and student feedback, which was used to improve the next cycle. Challenges that arose included limited time, resources, and teacher competency, but the ADDIE model provides a systematic framework to address these issues.